Auditory function in humans at high altitude. A scoping review. - Michela Masè; Andrea Viziano; Giacomo Strapazzon; Marco Alessandrini; Alessandro Micarelli (PLoS ONE)
Purpose High-altitude (HA) affects sensory organ response, but its effects on the inner ear are not fully understood. The present scoping review aimed to collect the available evidence about HA effects on the inner ear with focus on auditory function. Methods The scoping review was conducted following the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for scoping reviews. PubMed, Scopus, and Web of Science electronic databases were systematically searched to identify studies conducted in the last 20 years, which quantified in healthy subjects the effects of HA on auditory function. Results The systematic search identified 17 studies on a total population of 888 subjects (88.7% male, age: 27.8 ± 4.1 years; median sample size of 15 subjects). Nine studies were conducted in a simulated environment and eight during real expeditions at HA. To quantify auditory function, six studies performed pure tone audiometry, four studies measured otoacoustic emissions (OAE) and eight studies measured auditory evoked responses (AER). Study protocols presented heterogeneity in the spatio-temporal patterns of HA exposure, with highly varying maximal altitudes and exposure durations. Conclusion Most studies reported a reduction of auditory function with HA in terms of either elevation of auditory thresholds, lengthening of AER latencies, reduction of distortion-product and transient-evoked OAEs. Future studies in larger populations, using standardized protocols and multi-technique auditory function evaluation, are needed to further characterize the spatio-temporal pattern of HA effects along the auditory pathways and clarify the pathophysiological implications and reversibility of the observed changes.